HUMAN RESOURCE MANAGEMENT: APPLICATION OF THEORY AND PRACTICE IN INTERNAL ORGANIZATIONS - Wildan Army Adillah; M Zaky (Komitmen: Jurnal Ilmiah Manajemen, 2022)
Essentially, any business is dependent on human resources, which enable it to carry out a variety of operations to fulfill its objectives. This needs managers to actively manage and comprehend the people within the firm. Human resource management must be conducted properly and efficiently. Human Resource Management is dependent not only on management functions such as planning, organizing, implementing, controlling, and evaluating, but also on the implementation function of human resource management, including recruitment, selection, job evaluation, training and development, and how human resource management provides compensation. This is done in conformity with the Al-Qur'an and Hadith-based norms.